What she knew [large type] : a novel - Macmillan, Gilly (Thorndike Press, 2016)
In her gripping and skillful debut, Gilly Macmillan weaves a taut psychological thriller as she explores a mother's search for her eight-year-old son, missing after running ahead on an ordinary walk in the park on an ordinary Sunday.